1971
DOI: 10.1042/bj1240058p
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes as carriers of enzymes or drugs: a new approach to the treatment of storage diseases

Abstract: PROCEEDINGS OF THE BIOCHEMICAL SOCIETY medium nor by the liver. The experiments with amyloglucosidase showed no difference in glycogen concentration in the liver nor in glucose release into the medium when compared with control perfusions. Nevertheless there was penetration of liver tissue by circulating amyloglucosidase during perfusion corresponding to 0.03-0.4mg of enzyme/g wet wt. of liver (corrected for endogenous glucosidase activity). The concentration in liver was never greater than that in the medium.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(101 citation statements)
references
References 4 publications
0
97
0
4
Order By: Relevance
“…As noted previously, liposomes adopted as carriers for a variety of molecules [99,100] were shown to be effective as carriers of antigen and adjuvant compounds [101,102]. An extensive amount of work was completed in the 1980s and 1990s in a quest to optimize the adjuvant effects of liposomes.…”
Section: Rational Receptor-driven Adjuvantsmentioning
confidence: 92%
See 1 more Smart Citation
“…As noted previously, liposomes adopted as carriers for a variety of molecules [99,100] were shown to be effective as carriers of antigen and adjuvant compounds [101,102]. An extensive amount of work was completed in the 1980s and 1990s in a quest to optimize the adjuvant effects of liposomes.…”
Section: Rational Receptor-driven Adjuvantsmentioning
confidence: 92%
“…Liposomes adopted as carriers for a variety of molecules [99,100] were shown to be adjuvants as carriers of antigen and adjuvant agonists [101,102]. An alternative approach to targeting phagocytic cells, use of very slowly biodegradable methacrylate polymer nanospheres, was introduced by Kreuter and co-workers [103,104].…”
Section: Mechanistic Work By Mckinney and Davenportmentioning
confidence: 99%
“…19 Work from pioneers such as Gregoriadis, established how liposomes could enclose drugs to be used as DDS. 20,21 Others demonstrated that liposomes have the ability to change the in vivo distribution of entrapped drugs. 22 Many advances made during the late 1980s and early 1990s set the foundation to overcome many of the early challenges.…”
Section: A Evolution Of Liposomal Drug Targetingmentioning
confidence: 99%
“…The name still survives and has been counted in almost 40,000 publications in PubMed. The pioneering work of liposome researchers (Alec Bangham, Gregory Gregoriadis, Vladimir Torchilin, Demetrios Papahadjopoulos), at the early 1970s, established the concept of liposomes as drug delivery systems by demonstrating their ability to entrap drugs [6,7]. Their work, although is often forgotten, led to important technical advances for the development of liposome delivery systems, such as self-assembling, homogenization via extrusion, PEGylation for stability enhancement, active targeting by conjugating receptor antibodies, peptides or small cell ligands to the drug carrier.…”
Section: S10mentioning
confidence: 99%